Propuesta de Guía Didáctica para estimular la iniciación de la lectura en niños de 4 a 5 años de la Escuela de Educación Básica Nieto Caballero - Chango Andaluz, Gicela Aracely (2023)
Child stimulation is the application of techniques appropriate to the age of each child to encourage or strengthen the development of their abilities, especially the initiation of comprehension to written expression. This research proposes a didactic guide to stimulate the initiation to read, in children from 4 to 5 years of age, since there are shortcomings in the assimilation of reading in higher school years due to the deficiency in the use of strategies for stimulation in early ages. The present study has a mixed approach: qualitative, quantitative, and descriptive since through the information collected the characteristics of the object of study were analyzed. The instruments of the interview with the teacher, the survey to the parents of the family, and a checklist to the students were applied, in addition to the application of the statistical method for the collection and processing of data, the analysis was carried out to reach the conclusions. The population of the investigation is made up of 9 parents, 6 boys, 3 girls, and a teacher. The objectives set out in this investigation are for the benefit of the students since the didactic guide of activities is directed to them to stimulate the initiation to the reading for learning and academic development, thanks to the methods and strategies that will be applied by teachers, parents or people responsible for the growth of infants, adequate development of their potentialities and reading skills is achieved, for a school journey without annoyances.